The Types of Fish Caucht in Seagrass Areas in the Watersd of the Mie Strait, Moro District, Karimun Regency, Riau Islands Province - Zuli Meiryanti; Eddiwan Eddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Seagrass beds have a variety of important functions in the seagrass ecosystem, including nursery areas, feeding grounds, and protected areas. To find out the fish that live in seagrass ecosystem, gillnet and bubu trap are used. The results of the identification of fish species that live in the seagrass ecosystems in the Mie Strait waters found 30 species of fish. From the calculation of species dominance. The type of seagrass in the Mie Strait seagrass is one type of seagrass. One type of seagrass is Enhalus accoroide. The water quality of the noodle strait waters is as follows: temperature 30-30.5 0C, brightness 2.5-3 m, pH 7-8, salinity 30-31 ppt, dissolved oxygen 6.1-6.5 mg / L Keywords : Types of fish, seagrass, strait of noodles